The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/2053-1591/ab99e9
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and tensile properties of the different thickness ASSAPH440 high strength steel/DC52D+ZF45 galvanized cold rolled sheet dissimilar metal welding joint by CO2 laser welding for automobile manufacturing

Abstract: In order to adapt to the development trend of a lightweight automobile and meet the safety requirements of key automotive parts, it is necessary to study the relationship between microstructure and mechanical properties of the dissimilar and different thickness materials welded joint. In this work, a dissimilar welded joint of high strength vehicle steel ASSAPH440 with 2.0 mm thickness/ galvanized cold rolled sheet DC52D+ZF45 with 2.6 mm thickness formed by CO 2 laser welding was studied. The microstructure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Based on these results, microstructures and the determined mechanical properties indicate good weldability of this material, and hardening is occurred in the weld seam [19]. Luo et al [20] have performed experimental mechanical and metrological characterization of different thicknesses ASSAPH440 high strength steels welded by CO 2 laser welding and reported that the highest microhardness comes about at the center of the welding cross-section. In the same context, Chen et al [21] developed a vent hole in CO 2 laser welding to improve the welding quality and to minimize the porosities generation.…”
Section: Introductionmentioning
confidence: 95%
“…Based on these results, microstructures and the determined mechanical properties indicate good weldability of this material, and hardening is occurred in the weld seam [19]. Luo et al [20] have performed experimental mechanical and metrological characterization of different thicknesses ASSAPH440 high strength steels welded by CO 2 laser welding and reported that the highest microhardness comes about at the center of the welding cross-section. In the same context, Chen et al [21] developed a vent hole in CO 2 laser welding to improve the welding quality and to minimize the porosities generation.…”
Section: Introductionmentioning
confidence: 95%